(3cfR GdeYGfi aj TQM MQR GdCeGfis - (3eMeO Hf CMeO Hf eMeO GdehUdj GdMfHdj, CHh YHO Gddg, GdeYQha HTYdI, hjbGd dg GHf GdehbY,J (B656 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf Ydi SHYI CMQa hHYO heeG Ufa ai GdUfGYI GdTQjaI gh GdJCdja Gdefja GdehShe HMQR GdCeGfj s
(3BNQgG (B:s
(3hQRbfG TaGYJge jhe GdOjf, hgPG BNQ eG CQOfG ef EjVGM GdeYGfi dMQR GdCeGfi Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdKGfjs
(3GdfSNI HgG MhGTs
(3YdjgG HYV GdJedcGJs
(3cJHJ GdYfGhjf hCHjGJ GdbUjOI HGdMeQI s
(3fSNI SGOSI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdbQGAGJ hGdJLhjOs